2022
DOI: 10.18502/ijph.v51i11.11184
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Low Frequency Noise on Working Speed and Annoyance

Abstract: The Article Abstract is not available.  

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…This suggests that responses to LFN within the domain of higher-order cognitive functions are relatively consistent. Previous studies have demonstrated that low-frequency traffic noise slows down reading speed and negatively impacts performance in mathematical tasks [ 48 ] and that LFN can reduce mental arithmetic test accuracy [ 47 ]. Gao et al [ 51 ] observed a significant longitudinal negative correlation between traffic noise exposure and mathematical performance in cognitive testing.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that responses to LFN within the domain of higher-order cognitive functions are relatively consistent. Previous studies have demonstrated that low-frequency traffic noise slows down reading speed and negatively impacts performance in mathematical tasks [ 48 ] and that LFN can reduce mental arithmetic test accuracy [ 47 ]. Gao et al [ 51 ] observed a significant longitudinal negative correlation between traffic noise exposure and mathematical performance in cognitive testing.…”
Section: Discussionmentioning
confidence: 99%
“…Research on low-frequency sound (LFS), ranging from 15 Hz to 120 Hz, has primarily focused on low-frequency noise (LFN) [1,2], particularly the negative impact of LFS on human emotion perception or behaviors [3][4][5], e.g., the sense of noise in LFS is the main factor that incurs the perception of annoyance. Experimental comparisons have shown that LFS is more strongly associated with annoyance than other types under the same sound pressure level [6].…”
Section: Introductionmentioning
confidence: 99%